Pneumatic battery for untethered robotic gripper with the influence of low molecular weight solid electrolyte - Norman Aliff Azman (Nanyang Technological University, 2022)
Conventional robotic grippers are considered tethered devices due to needing to be connected to a pressurized gas supply line or compressed gas tank, resulting in limited mobility. The limited mobility would make the robotic gripper more suitable for stationary applications. To achieve an untethered robotic gripper, an alternative power source would be required to help convert electrical energy to chemical energy to finally mechanical energy without a motor or compressor. An electrochemical pneumatic battery (EPB) could serve as a portable power source to support the untethered operation of pneumatically driven robotics. The Zinc-air battery-based EPB can be flexible and portable to allow easy attachment and detachment, and thus the robotic gripper can be untethered. So, a solid electrolyte was looked into to achieve a solid-state zinc-air battery that serves as the flexible and portable EPB power source. Similar to the power source, a flexible and portable control unit must also be considered. A PLC and a solenoid valve were then used to design a control unit for the robotic gripper due to its compactness and ability to make a device or system automated. For this report, a solid electrolyte was fabricated using polyvinyl alcohol (PVA) with a molecular weight of 13000~23000, and parameters were defined before fabrication started. The solid electrolyte was then measured, and the results were obtained and discussed. Some of the samples of solid electrolytes were able to produce a voltage higher than the practical voltage from previous research. A schematic design for the connection of the PLC to the solenoid valve is shown in this report.